On Designing Prototype Model of “MathWiz” Mobile Application as an AR-Based Learning Media to Improve Students’ Mathematical Proficiency - Luki Luqmanul Hakim; Ahmad Salmun; Yayu Laila Sulastri (Jurnal Indonesia Sosial Sains, 2024)
Learning loss is one type of learning crisis, which refers to the loss of previously learned competencies, incomplete learning at the grade level, and the numerous consequences of not mastering learning at each grade level. As a result, attempts can be made to address these issues through advancing information technology, particularly through augmented Reality (AR)-based learning technologies and artificial intelligence with machine learning. This study aims to create and evaluate the effectiveness of the mobile application "MathWiz" as an AR-based learning media for improving students' mathematical proficiency. The MathWiz program is designed in three stages: listen to customers, build/revise mock-ups, and customer test drives mock-ups. Many respondents from several universities in Bandung participated in this study. According to the results, MathWiz has four advantages: (1) it can display detailed objects and learning materials in real-time; (2) interactivity supported by sophisticated and accurate audio text, video, images, and animation features; (3) has the potential to improve students' mathematical proficiency, and (4) has the potential to increase students' interest in learning mathematics and reduce boredom. The results of this study show that learning mathematics can be made more entertaining and memorable through lecturer innovation.